Intramedullary nailing for femoral shaft fractures in adults - Xiong, Ran (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects (benefits and harms) of different methods of intramedullary nailing for femoral shaft fractures in adults.